Towards the development of a robust model hierarchy: investigation of dynamical limitations at low resolution and possible solutions. (7th June 2012) - Sanchez, Claudio; Williams, Keith D.; Shutts, Glenn J.; McDonald, Ruth E.; Hinton, Tim J.; Senior, Cath A.; Wood, Nigel
Abstract In order to investigate questions concerning changes in the atmosphere and other components of the Earth system, it is desirable to have a seamless modelling system that operates across a wide range of time‐scales and horizontal resolutions. The development of a low‐resolution configuration of the model would greatly assist in addressing these scientific questions whose long time‐scales or complexity are computationally demanding—a cost that cannot be sustained by higher resolutions. However, in order to be confident that results remain robust to changes in resolution, it is essential that such models include the same underlying fundamental processes as those at higher resolution. Some resolution‐dependent biases are found to grow (notably when horizontal resolution decreases below ∼150 km) as a result of the lack of transient eddy kinetic energy (TEKE). The advection scheme used by many of the current general circulation models follows the semi‐Lagrangian (SL) dynamics approach. Because of the need for interpolation to the departure point, the scheme is highly diffusive when low‐order interpolation schemes are used. We analyse how the impact of the high diffusivity of SL schemes leads to a lack of TEKE, which inhibits the development of mid‐latitude variability phenomena such as synoptic cyclones or blocking events. Conversely, some examples where the performance of the low resolution is acceptable are provided. We investigate two different traceable solutions to partially offset the misrepresentation of dynamical features in the low‐resolution version: a change of the interpolation scheme from quasi‐cubic to quintic interpolation; and vorticity confinement: a parametrization designed to preserve vorticity features in dissipative numerical schemes. Both solutions are found to increase TEKE and improve many of the mid‐latitude metrics considered. Copyright © 2012 British Crown copyright, the Met Office. Published by John Wiley & Sons Ltd.